Knowledge Management and Ontology - Tiberiu SOCACIU; Paul PASCU (USV Annals of Economics and Public Administration, 2016)
The knowledge society characteristic to the XXI century derives from the information society but is more than this and focuses on how information becomes knowledge. Fulminating evolution of this society has enabled intelligent devices (be they desktops, laptops, tablets, smart phones and others) to be part of everyone's life. These tools not only facilitate rapid access to information, which is considered the most valuable thing today but through the multitude of applications, we can ease the decisions we make every day. In this context our approach aims at building an ontology using OWL (Web Ontology Language) and RDF (Resource Description Framework) in economic and a platform for working with ontologies. The platform will be represented by a web application and will allow users to extend an ontology by adding new concepts such as classes, subclasses, individual properties, but also to see ontology as a knowledge graph. Also users will be able to interact with the ontology by interrogating it using SPARQL language. Consequently, I believe that the proposed application is meant to be a useful application for viewing, querying and extending ontologies.